Sakamoto days. Vol. 6, Bad luck - Suzuki, Yūto (Shonen Jump manga., 2023)
"Taro Sakamoto was once a legendary hit man considered the greatest of all time. Bad guys feared him! Assassins revered him! But then one day he quit, got married, and had a baby. He's now living the quiet life as the owner of a neighborhood store, but how long can Sakamoto enjoy his days of retirement before his past catches up to him?! Dangerous serial killers clash with the Order and Sakamoto's crew! As the battles rage on, Sakamoto undergoes an unexpected transformation. Meanwhile, the evil mastermind X reveals his true intent, which sends shock waves through the assassin world!"--Back cover.